A Blockchain-Based Architecture for Communication Between Spectrum Access Systems - Veloso, Alan; Sousa, Jeffson; Abreu, Diego; Freitas, Allan; Abelém, Antônio (Anais do Latin-American Symposium on Dependable Computing (LADC), 2025)
This paper proposes an architecture for Spectrum Access Systems (SAS) integrated with permissioned blockchain technology to enhance security, traceability, and interoperability in the communication among different SAS instances. The approach leverages smart contracts to automate data usage agreements, device registration, and spectrum coordination, replacing traditional Representational State Transfer (REST) interfaces with a distributed and auditable infrastructure. The proposed model is validated through a practical implementation using Hyperledger Besu, demonstrating feasibility and compliance with regulatory requirements. The hybrid solution offers advantages such as data immutability, shared governance, and operational resilience.